1995
DOI: 10.1111/1523-1747.ep12320803
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Detection of Epidermodysplasia Verruciformis–Associated Human Papillomavirus DNA in Biopsies from Malignant and Premalignant Skin Lesions from Renal Transplant Recipients

Abstract: Based on immunologic and epidemiologic data, it is plausible that skin cancer in renal transplant recipients is associated with human papillomaviruses (HPV). At present, conflicting evidence exists concerning the presence of HPV DNA in these cancers. We recently described a nested polymerase chain reaction method that enables the detection of all previously isolated epidermodysplasia verruciformis (EV)-associated HPVs. We now describe the detection of EV-associated HPV DNA in 49 (80%) of 61 biopsies from squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
112
0
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 20 publications
10
112
0
4
Order By: Relevance
“…The cancers in EV individuals predominantly occur at body sites exposed to sunlight, pointing to a role for ultra violet (UV) radiation in the development of the disease (Orth et al, 1979). In addition to EV, a role for HPVs has also been postulated in the development of non-melanoma skin cancers (NMSC) in both immunocompetent and immunocompromised individuals, such as organ transplant recipients (Jablonska, 1990;Purdie et al, 1993;de Jong-Tieben et al, 1995;Shamanin et al, 1996;Hop¯et al, 1997;Surentheran et al, 1998). Interestingly, these individuals also often develop NMSC at UV-exposed sites (reviewed in Proby et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cancers in EV individuals predominantly occur at body sites exposed to sunlight, pointing to a role for ultra violet (UV) radiation in the development of the disease (Orth et al, 1979). In addition to EV, a role for HPVs has also been postulated in the development of non-melanoma skin cancers (NMSC) in both immunocompetent and immunocompromised individuals, such as organ transplant recipients (Jablonska, 1990;Purdie et al, 1993;de Jong-Tieben et al, 1995;Shamanin et al, 1996;Hop¯et al, 1997;Surentheran et al, 1998). Interestingly, these individuals also often develop NMSC at UV-exposed sites (reviewed in Proby et al, 1996).…”
mentioning
confidence: 99%
“…These patients are exposed to chronic as well as acute UV doses and whose cutaneous lesions, including both warts and cancers, frequently harbour a diverse spectrum of HPV sequences (Shamanin et al, 1994(Shamanin et al, , 1996Berkhout et al, 1995;de Jong-Tieben et al, 1995). Although HPV10 is usually associated with benign proliferations in immunocompetent and immunosuppressed individuals (Favre et al, 1989;Obalek et al, 1992;Shamanin et al, 1994) it has also been found in carcinomas in organ transplant recipients in which the lesions are often multiply infected (Storey et al, 1998).…”
mentioning
confidence: 99%
“…In organ-transplant recipients, b-HPV DNA is frequently detected in skin cancer and its precursor lesions, mainly actinic keratoses, suggesting a role for b-HPVs in skin cancer development (Berkhout et al, 2000;de Jong-Tieben et al, 1995;Harwood et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In kidney graft recipients, the relative risk of development of skin carcinomas is 10 to 250 times higher than in matched controls (4). UV-induced mutations (5,6), human papillomavirus infections (7,8), and immunodepression have been implicated in the pathogeny of these tumors. Occurrence of carcinomas is also correlated with human leukocyte antigen B mismatching between donor and recipient (9) suggesting the involvement of immunologic phenomena.…”
Section: Introductionmentioning
confidence: 99%